The Effect of Inflation, Exchange Rate, and BI Rate on the Indonesian Sharia Stock Index (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
Islam strongly advises against investment, as mentioned in lines 46–49 of the Surah Yusuf. The Islamic stock market, which offers Islamic stocks as one of its components, is one place where somebody can invest. Several macroeconomic and microeconomic factors, as well as equity investment, have an impact on Islamic stocks. This study examined the impact of inflation, exchange rates, and the BI Rate on the Indonesian Sharia Stock Index (ISSI) throughout the years 2017–2021. Statistical data on the market capitalization of the Indonesian Sharia Stock Index (ISSI) given at the Financial Services Authority (OJK), as well as other variables like inflation, currency rates, and the BI, were used in the quantitative research technique. Analysis of the research data was carried out through multiple linear regression modeling. The results showed that the Inflation variable (X1) had no effect on the Indonesian Sharia Stock Index (ISSI), the Exchange Rate variable (X2) had a significant negative effect on the Indonesian Sharia Stock Index (ISSI) and the BI Rate variable (X3) had an effect significantly positive to the Indonesian Sharia Stock Index (ISSI). The macroeconomic variables used in this study have an impact on the movement of the Islamic stock index, which causes the movement of the ISSI to vary quite a bit.